Applying social-ecological system resilience principles to the context of woody vegetation management in smallholder farming landscapes of the Global South - Shumi, Girma; Loos, Jacqueline; Fischer, Joern (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
Woody vegetation diversity is declining due to human-induced land-use changes, mainly agricultural expansion and intensification, deforestation, forest degradation and urbanisation. This loss challenges the resilience and sustainability of smallholder farming landscapes, in which woody vegetation plays an important role for the provision of multiple material and non-material benefits to people and nature. In this review, we examine the relevance and application of established social-ecological resilience principles to woody vegetation management and explore how the resilience of smallholder farming landscapes can be enhanced in the Global South. To this end, we conducted a qualitative review and purposefully selected scientific literature relevant to each resilience principle. Exemplified by different cases from across the Global South, we collate evidence for the significance of all principles for woody vegetation management. Our review also sheds light on widespread obstacles to sustainable woody vegetation management and landscape resilience, such as the pursuit of top-down and sectoral policies for agriculture and woody vegetation management, deep-rooted power dynamics and asymmetries, and the marginalisation of local people and their traditional knowledge systems. Applying resilience principles to woody vegetation management in smallholder farming landscapes therefore requires transformative changes that enable paradigm shifts, for example, through more genuine recognition of local people and their livelihoods, knowledge and experiences.
Keywords: Ecosystem Service; Global South; Local People; Social-ecological System; Resilience Principle; Woody Vegetation Management; 630 Landwirtschaft und verwandte Bereiche